2014
DOI: 10.1002/art.38874
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth and Preterm Birth in Children Exposed to Maternal or Paternal Rheumatoid Arthritis: A Nationwide Cohort Study

Abstract: Objective To assess indicators of fetal growth and risk of preterm birth in children of parents with rheumatoid arthritis (RA). Methods Through linkage of Danish national registries we identified all children born in Denmark between 1977 and 2008. We used general linear regression models to estimate mean differences in indicators of fetal growth among children having a parent with RA compared to unexposed children. Odds ratios of preterm birth were calculated by a logistic regression model. Results Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 49 publications
1
48
0
2
Order By: Relevance
“…Moreover, compared with controls, and after correction for multiple comparisons, moderate/severe complications of pregnancy were significantly more common only in the group of cases with persistence of rheumatic symptoms. A large, epidemiologic, population-based retrospective study in Denmark found that children exposed to preclinical maternal rheumatoid arthritis were more often born preterm and with a placental and neonatal weight lower than that recorded among unexposed controls (31). Finally, the so-called non-criteria APS, that is the presence of incomplete clinical and/or laboratory manifestation of APS, is associated with an increased risk of pregnancy complications, such as recurrent fetal loss and adverse pregnancy outcomes mediated by placental insufficiency (25).…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, compared with controls, and after correction for multiple comparisons, moderate/severe complications of pregnancy were significantly more common only in the group of cases with persistence of rheumatic symptoms. A large, epidemiologic, population-based retrospective study in Denmark found that children exposed to preclinical maternal rheumatoid arthritis were more often born preterm and with a placental and neonatal weight lower than that recorded among unexposed controls (31). Finally, the so-called non-criteria APS, that is the presence of incomplete clinical and/or laboratory manifestation of APS, is associated with an increased risk of pregnancy complications, such as recurrent fetal loss and adverse pregnancy outcomes mediated by placental insufficiency (25).…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies have linked maternal RA with preterm birth [3-8] and low birth weight [5,6,8-11]. These associations could be caused by fetal programming induced by the disease, prenatal exposure to RA treatment or be related to genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…RA must be controlled while patients are attempting to conceive, and time to conception is longer in those with higher disease activity [27]. In addition, patients with RA are more likely to have preterm births [28]. Elevated disease activity during pregnancy is associated with rapid postnatal catch-up growth in offspring, a risk factor for cardiovascular disease in adulthood [29].…”
Section: Discussionmentioning
confidence: 99%